The Respect of Recommendations Provided in an International Travelers' Medical Service: Far From the Cup to the Lips. Issue 2 (27th November 2012) - Muller, Jean Michel; Simonet, Anne Laure; Binois, Raphaelle; Muggeo, Elisabeth; Bugnon, Pierre; Liet, Jérome; Duong, Michel; Chavanet, Pascal; Piroth, Lionel
<x xml:space="preserve">Abstract</x> Background It is not clearly known how frequently the recommendations given to travelers are followed, and what factors could encourage compliance with these recommended measures. Methods Adults consulting at a Medical Department for International Travelers (International Travelers' Medical Services, ITMS) in October and November 2010 were asked to answer a questionnaire before their journey. They were also contacted for a post‐travel telephone interview to determine whether they had followed the recommendations regarding vaccinations and malaria prevention, and the reasons for poor or noncompliance with these recommendations. Results A total of 353 travelers were included, with post‐travel data available for 321 of them. Complete compliance with all the recommendations (vaccinations and malaria chemoprophylaxis) was observed in 186/321 (57.9%) of the travelers. Only 55.6% (233/419) of the prescribed vaccinations were given, with huge variability according to the type of vaccine. Only 57.3% (184/321) of the patients used a mosquito net. Among the 287 prescriptions for antimalarial drugs, 219 (76.3%) were taken correctly, 37 (12.9%) were taken incorrectly (noncompliance with the duration and/or dosage), and 31 (10.8%) were not taken at all. Traveling to areas of mass tourism (Kenya/Senegal), consulting their general practitioner (GP), and being retired were significantly and independently associated with better overall compliance in univariate and multivariate analyses. Conclusions Compliance could be improved by focusing on factors associated with poor compliance to improve the advice given to less compliant travelers, by providing clear information tailored to each traveler, with a focus on key messages, and by improving coordination between ITMS and GPs.